Caracterização molecular de um novo alelo do gene ZmMATE1 que confere tolerância ao alumínio em milho - Marcella Baroni de Resende Costa (2017)
One of the major constraints to grain yield in tropical countries is the aluminum (Al) toxicity on acid soils, which limits root growth and impairs water and mineral nutrient uptake. In maize (Zea mays L.), Al tolerance is a complex trait that involves several genes, of which ZmMATE1 was the only one characterized as responsible for Al tolerance. This gene is homolog to sorghum SbMATE, which encodes a membrane transporter that mediates citrate exudation in root apices and forms stable non-toxic compounds when combined with Al3+ in the soil solution. The occurrence of three copies in tandem of ZmMATE1 was associated with high levels of expression of this gene and with Al tolerance in a population derived from Cateto Al237, a highly Al-tolerant line. Nonetheless, the maize line L228-3 shows only one copy of ZmMATE1 and high expression levels of this gene, comparable to those observed in Cateto Al237. Therefore, this study aimed to characterize the molecular basis of the ZmMATE1 allele derived from the elite maize line L228-3. Regression analysis between a molecular marker in the ZmMATE1 promoter region and the relative growth of the seminal root showed that the allele derived from L228-3 was responsible for 22.17% of Al tolerance in an F2 population. A detailed expression analysis showed that this allele was induced by Al after 1 hour in the root tips and in the rest of the root, showing an expression profile similar to the allele derived from Cateto Al237. Sequencing and in silico predictions of -2710 base pairs to the start codon of ZmMATE1 identified a SNP (Single Nucleotide Polymorphism) between L53 and the Al-tolerant lines flanking or co-localized to conserved binding regions of transcription factors, suggesting that this SNP may control ZmMATE1 expression. Amplification, cloning and sequencing of the 5' untranslated region (5'UTR) revealed the presence of different transcriptional start sites for ZmMATE1, once fragments of different sizes and polymorphisms were identified among the three lines. These results indicate a possible control of ZmMATE1 expression. Finally, the expression pattern of candidate genes encoding transcription factors with sequence similarity to STOP1, ART1, SbZNF1 and SbWRKY1 were evaluated. These transcription factors regulate the expression of genes involved in the Al tolerance in other species. One of the genes with DHHC domain presented an expression profile compatible with a putative repressor of ZmMATE1 expression. Thus, these results are new targets for complementary studies aiming to disclose the mechanisms controlling ZmMATE1 expression and Al tolerance in maize.